Emergence of chemoresistance in a metastatic basal cell carcinoma patient after complete response to hedgehog pathway inhibitor vismodegib (GDC‐0449). (August 2014) - Meani, Rowena E; Lim, Shueh‐Wen; Chang, Anne Lynn S; Kelly, John W
Abstract Vismodegib (GDC‐0449, Genentech, USA), a small molecule inhibitor of the Hedgehog signalling pathway, has potent anti‐tumour activity in advanced basal cell carcinoma (BCC). We report a case of a 67‐year‐old Australian man with metastatic BCC including pulmonary disease with malignant effusion who showed a dramatic complete response to vismodegib but subsequently experienced a recurrence of pulmonary disease, indicative of chemoresistance to vismodegib. This case is the first to illustrate chemoresistance in a patient with metastatic BCC, and demonstrates the need for closely monitoring metastatic BCC patients even after an apparently complete response.